PATTERN OF ABDOMINAL VISCERA INJURIES IN BLUNT ABDOMINAL TRAUMA DEATHS IN AHMEDABAD (Journal of Forensic Medicine & Toxicology, 2019)
In this age of speed and traffic accidents, the incidence of blunt injuries to the abdomen has been at its height due to the development of the modern industrial era with the development of the automobile. This study was conducted to describe the frequency and pattern of intra-abdominal injuries in patients with blunt abdominal trauma. The present study was undertaken on 693 victims who died due to blunt abdominal injuries which were autopsied at B. J. Medical College mortuary, Ahmedabad during the year 2016-2017. This study shows that most common organ involved in blunt abdominal injuries is liver. Most common associated injuries with this is chest injuries. Highest number of people died due to shock and hemorrhage.
Keywords: Blunt abdominal trauma; Intra-abdominal injuries